Cognitive Strategies of Second Language Vocabulary Inferencing: An Eye Tracking Study - Anna Izmalkova; Irina Blinnikova (MDPI AG, 2024)
In contextual vocabulary acquisition, second language learners address both morphological and contextual cues to infer the meanings of novel words. The study investigated cognitive strategies and their eye movement correlates in contextual vocabulary inferencing task. A sample of 30 healthy participants with normal or corrected to normal vision read an Intermediate-level text in English, aiming to define the meaning of 10 low-frequency words embedded in the text. Based on both unstructured and structured post-hoc reports, we attributed the inferencing process either to word-level processing, context-level processing, or discourse-level processing strategy. Eye movements were recorded on the target word and on the target word clause areas of interest. Inferencing success was associated with increased first fixation duration on the target word both for word- and context-level processing strategy, and increased dwell time on the target word clause for context-level processing strategy. Our findings emphasize the role of both morphological and contextual processing in vocabulary inferencing task.